Pre‐exposure prophylaxis initiation and adherence among Black men who have sex with men (MSM) in three US cities: results from the HPTN 073 study. Issue 2 (15th February 2019) - Wheeler, Darrell P; Fields, Sheldon D; Beauchamp, Geetha; Chen, Ying Q; Emel, Lynda M; Hightow‐Weidman, Lisa; Hucks‐Ortiz, Christopher; Kuo, Irene; Lucas, Jonathan; Magnus, Manya; Mayer, Kenneth H; Nelson, LaRon E; et al.
Abstract: Introduction: Randomized clinical trials have demonstrated the efficacy of antiretroviral pre‐exposure prophylaxis (PrEP) in preventing HIV acquisition among men who have sex with men (MSM). However, limited research has examined initiation and adherence to PrEP among Black MSM (BMSM) in the United States (US) who are disproportionately represented among newly HIV infected and late to care individuals. This research reports on the HIV Prevention Trials Network 073 (HPTN 073) study aimed to examine PrEP initiation, utilization and adherence among Black MSM utilizing the theoretically principled, culturally informed and client‐centered care coordination (C4) model. Methods: The HPTN 073 study enrolled and followed 226 HIV‐uninfected Black MSM in three US cities (Los Angeles, CA; Washington DC; and Chapel Hill, NC) from February 2013 through September 2015. Study participants were offered once daily oral emtricitabine/tenofovir (FTC/TDF) PrEP combined with C4 and followed up for 52 weeks. Participants received HIV testing, risk reduction education and clinical monitoring. Results: Of the 226 men enrolled, 178 participants initiated PrEP (79%), and of these 64% demonstrated PrEP utilization at week 26 (mid‐point of the study) based on pharmacokinetic testing. Condomless anal sex with an HIV‐infected or unknown status casual male partner was statistically significantly associated with a greater likelihood of PrEP initiation (adjusted odds ratio (OR) 4.4, 95% confidence interval (CI) 1.7, 11.7). Greater age (≥25 vs. <25, OR 2.95, 95% CI 1.37 –6.37), perception of having enough money (OR 3.6, 95% CI 1.7 to 7.7) and knowledge of male partner taking PrEP before sex (OR 2.22, 95% CI 1.03 to 4.79) were statistically significantly associated with increased likelihood of PrEP adherence at week 26. Annualized HIV incidence was 2.9 (95% CI 1.2 to 7.9) among those who initiated PrEP, compared to 7.7 (95% CI 2.5 to 24.1) among those who did not initiate PrEP ( p  = 0.18). Conclusions: Results suggest a high level of PrEP initiation among at‐risk Black MSM, a group historically characterized as hard to reach. The data support the importance of addressing contextual factors that affect PrEP initiation and adherence, and of additional research on the ultimate benefit of PrEP in HIV prevention among Black MSM.